The city as an educational field (Journal of Parents and Teachers, 2014)
The city is where we can learn art, history, sport, religion, economy and knowledge of the environment, among many others. Also, in the city we can also learn citizens' values to improve the coexistence and know our own rights and others’.
Keywords: city; areas of knowledge; culture; coexistence; society.